Without Creative Destruction and Creative Construction? The Evolution if Triple Helix in Croatia - Lažnjak, Jasminka (Array, 2005)
The main thesis is that in Croatia as post socialist, transition countries, TH model is not developed yet, at least not on significant level and exist only as exceptional cases. To illustrate this statement paper gives an overview of research industry cooperation. The second issue of the paper is to investigate the causes of the state of the art in the wider social context and establish how socio economic system enables or disables the evolution of TH. For this purpose, the two helices of TH are analyzed in given social context, government and university. In the concluding part of the paper on the basis of diagnosis some implications for more pro active innovation policy are given.